Pengembangan E-book “EFIKA” Sebagai Media Pembelajaran Materi Kalimat Efektif - Permatasani, Indah; Djuanda, Dadan; Gustian Nugraha, Rana (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2026)
This study was motivated by the low ability of students to construct effective sentences in narrative writing activities and the limited use of interactive digital learning media in Indonesian language instruction at the elementary school level. Therefore, a learning medium is needed to help students understand the concept of effective sentences in a more engaging and effective way. This study aimed to describe the development process of the “EFIKA” (Effectiveness of Sentences) e-book on effective sentence materials and to analyze the feasibility and practicality of the developed media. The research employed a Design and Development (D&D) approach using the 4D development model, which consists of the Define, Design, Develop, and Disseminate stages. The trial was conducted with 30 fourth-grade students at SDN Manangga. The results showed that the material expert validation achieved a percentage of 96.9%, categorized as “feasible for use without revision.” Media expert validation obtained percentages of 92.5% and 95%, both categorized as “feasible for use without revision.” The teacher response results reached 100%, categorized as “very practical,” while the students’ responses obtained an average percentage of 91.74%, also categorized as “very practical.” Based on these findings, it can be concluded that the “EFIKA” e-book is feasible and highly practical to be used as a learning medium in Indonesian language learning, particularly on effective sentence materials, to support elementary school students’ writing skills.